Molecular systematics of Mahseers (Cyprinidae) in Malaysia inferred from sequencing of a mitochondrial Cytochrome C Oxidase I (COI) gene - Esa, Yuzine; Siraj, Siti Shapor; Daud, Siti Khalijah; Japning, Jeffrine Rovie Ryan; Abdul Rahim, Khairul Adha; Tan, Soon Guan (Universiti Putra Malaysia Press, 2008)
This study examined the molecular systematics among three Mahseers (Tor douronensis, Tor tambroides and Neolissochilus stracheyi) using partial sequencing of a Cytochrome C Oxidase I (COI) mitochondrial DNA segment (466bp). The phylogenetic results using the Neighbour-Joining (NJ) method supported the monophyletic status (hence the taxonomic status) among the three putative Mahseer species. The close genetic relationships (0.1- 0.4%) found between T. tambroides samples from Peninsular Malaysia (kelah fish) and those from Sarawak (empurau fish) also supported their classification as belonging to the same species. The phylogenetic analysis also showed that the T. douronensis mtDNA consisted of three highly distinct lineages supported by high bootstrap values, with the Sabah samples forming its own cluster. Thus, this phylogenetic study, although based on a limited number of samples and only a single mtDNA gene managed to provide useful insights into the systematic status of the Mahseers found in Malaysia.